Climate Change and Air Pollution Dynamics: Synergistic Effects and Mitigation Strategies - Sunidhi Chauhan (International Journal of Environmental Noise and Pollution Control, 2025)
Climate change and air pollution are deeply interlinked environmental problems that jointly exacerbate human health, ecosystem integrity, and economic well‑being. As global temperatures rise, shifts in meteorological conditions—such as increased heat, altered precipitation, and more frequent extreme weather events—modify pollutant generation, dispersion, chemical transformation, and removal processes. Meanwhile, many sources of air pollution are also sources of greenhouse gases (GHGs), giving rise to potential co‑benefits or trade‑offs when formulating mitigation strategies. This review synthesizes recent evidence on the synergistic dynamics between climate change and air pollution, examines current mitigation strategies that address both issues, highlights limitations in existing studies, and proposes future directions. Key findings indicate that heat amplifies the mortality and morbidity effects of particulate matter (PM₂.₅) and ozone, particularly during heat wave episodes; wildfires and biomass burning—heightened by climate change—contribute large episodic emissions of both short‑lived climate pollutants (SLCPs) and conventional pollutants; and changes in atmospheric chemistry, such as higher water vapor and solar radiation, promote ozone formation under warmer conditions. Mitigation measures such as transitioning from fossil fuels to renewables, implementing SLCP‑targeted controls (e.g., black carbon, methane), improving energy efficiency, adopting clean transport policies, and enhancing land management and urban planning exhibit strong potential for joint benefits. However, uncertainties remain in projections due to variability in emission pathways, regional heterogeneity in climate and pollutant responses, limited integration of co‑exposures (e.g., heat + pollution + allergens), lack of high‑resolution data, and insufficient understanding of non‑linear interactions. In conclusion, despite challenges, there is considerable scope to design integrated policies that deliver health, environmental, and climate gains simultaneously. Future research should focus on region‑specific modeling, improved exposure assessment (especially for vulnerable populations), exploring feedback loops (e.g. pollution → climate change → pollution), and refining cost‑benefit analyses to guide decision‑making.
Keywords: Air pollution; Climate change; Co benefits & mitigation strategies; Health impacts; Ozone & particulate matter; Short lived climate pollutants (SLCPs); Synergistic effects